STRUCTURAL ANALYSIS OF PUTU WIJAYA'S “OPERASI" DRAMA SCRIPT AS AN ALTERNATIVE INDONESIAN LANGUAGE TEACHING MATERIAL - Siti Papat Patimah; Salma Nurfadillah; Zakia Nur Huda; Adita Widara Putra (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
The structural approach has been widely used by researchers to reveal the implied meaning in a literary work. Drama as a literary genre is built by physical elements that bind each other into one complete story so that it can be acted out in a drama performance. This research aims to analyze the structure of the drama script "Operasi" by Putu Wijaya. A structural approach is used to identify and describe the intrinsic elements that make up the entire text of a drama script. The elements analyzed include theme, plot, characters and characterization, setting, dialogue, message, and so on. In-depth analysis of a script's structure helps understand how the story is structured, conflict develops, characters develop, and themes are conveyed. This analysis uses a qualitative descriptive research method by utilizing qualitative data and describing it descriptively. The aim of this research is to reveal how the drama script "Operasi" is a reflection of society and current social conditions through the structure of its construction. Apart from that, its relevance to learning in schools can develop a deeper understanding of literary works. This scientific article highlights the artistic excellence of manuscripts and the importance of understanding structural analysis in appreciating and interpreting literary works. It is hoped that the results of the structural analysis of the drama script "Operasi" by Putu Wijaya will be able to add to the literature for further research.